A novel cross-institutional college internship program to train future diverse leaders in clinical research with data-driven approaches to assess impact - Derk, Julia; Dzirasa, Kafui; Locklear, Tracie (Frontiers in Pharmacology, 2023)
The field of Clinical Research, like many other scientific disciplines, has struggled to recruit and retain talented researchers from diverse communities. While there is a strong history of documenting the problem, having a diverse and inclusive workforce is hindered by the lack of data-driven approaches, cross-institutional partnerships, access to mentors, and positive immersive experiences for people from underrepresented groups. Here, we describe a novel initiative for North Carolina Central University (NCCU) Clinical Research Sciences Program to partner with Duke University for a 15-week internship for graduating seniors to receive a Bachelor of Science in Clinical Research. The goals of the internship are: 1) to give hands-on training to enhance the impact of classroom-based learning, 2) broaden their understanding of the wide swath of positions available to them, 3) promote their sense of self-efficacy, confidence, science identity, research identity, and connections to the pre-clinical and clinical community, and 4) prepare them to be workforce ready upon graduating. The students will be at Pickett Road and The Collective for Psychiatric Neuroengineering. They will also receive eight one-hour professional development training sessions and five one-hour sessions based on the Entering Research Curriculum developed by the Center for the Improvement of Mentored Experiences in Research (CIMER). These student-interns will perform pre-and post-internship self-assessment surveys to quantify their self-efficacy, feelings of belonging, access to research opportunities and mentors, and to give details of their future education and career goals. Collectively, these approaches will help recruit and train talented and diverse leaders within clinical research.